Large-area surface wave plasma source - Azarenkov, N.A.; Bizyukov, A.A.; Sereda, K.N.; Tseluyko, A.Ph.; Yunakov, N.N.; Gapon, A.V.; Kashaba, A.Y. (Вопросы атомной науки и техники, 2002)
A surface wave plasma source for the production of a large-diameter, high electron density and low electron temperature plasma at low pressure without using a magnetic field for plasma processing and thin film preparation are. The DC or RF voltage with the frequency of 13.56 MHz can supply the source. The pumping-out of the source is carried out through the insulated substrate holder. The plasma source operates in a working gas pressure range of 3∙10⁻² ÷ 10⁻⁴ Torr with changing the RF power in a range of 50÷1000 W during the discharge on surface waves with the mode 0 excited by a ring antenna. The plasma density has a homogeneous distribution over a diameter of 300 mm and varies in a range of 10⁸÷10¹⁰ cm⁻³ at electron temperature of 2÷7 eV depending on external parameters. An ion beam density in the presence of the RF bias applied to the substrate holder reached 0.1 mA/сm² with homogeneous distribution over the diameter of 300 mm. The total ion current to the substrate holder with a diameter of 467 mm reaches the value of 2 A with average ion energy of 200 eV. Numerical analysis of electric field distribution over the processing chamber in linear approach was made and compared to experimental results obtained.